Macular Retinal Microvasculature of Hyperopia, Emmetropia, and Myopia in Children - Lv, Liang; Li, Mu; Chang, Xuejiao; Zhu, Mengxia; Liu, Ying; Wang, Ping; Xiang, Yan (Frontiers in Medicine, 2022)
Purpose: To compare macular retinal microcirculation in myopia, emmetropia, and hyperopia groups and investigate the relationship between macular retinal microcirculation and axial length (AL) in children. Methods: Forty myopic, 29 emmetropic, and 34 hyperopic eyes were included. All the recruited eyes underwent optical coherence tomography angiography (OCTA) examinations. After adjusting the image size by the Littmann method and Bennett formula, the vessel density (VD) of the deep capillary plexus (DCP) and superficial vascular plexus (SVP) were assessed. Results: The VD of the DCP was significantly lower in the myopia group than in the hyperopia group, whereas no significant differences in the VD of the SVP were observed among the myopia, emmetropia, and hyperopia groups. The VD of the DCP was significantly associated with AL, spherical equivalent (SE), and foveal retinal thickness (FRT), whereas the VD of the SVP was only significantly associated with FRT, but not with AL or SE. Conclusions: The myopic VD of the DCP was significantly lower than the hyperopic one, and the VD of the DCP was significantly associated with AL, indicating that myopia has a lower VD of the DCP, and AL could have a negative effect on the VD of the DCP. Thus, early myopic axial stretching might decrease retinal blood perfusion of the DCP in children.